(3GdHjGf hGdJHjf aj GdCfJUGQs - (3RgQ Hf YHO Gdedc Hf eMeO Hf RgQ GdGTHjdj, CHh GdYdGA,J (B525 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GJbf cd TFNdbg CeG HYO aEfg deG cGf GdEfSGf eMHhdkG Ydi MH GdHbG hGdQZHI Yf GdafG s
(3BNQgG (B:s
(3bO aYdJ Pdc hEfgG JMJGL Edi Pdc GdCHOGf dcKQI GdaVd GdJi dGjh ef Gf YdfjG hEMSGfkG ZdjgG Je GdWH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI eTgO (B- (3cdjI GdGdgjGJ s
Keywords: (3GdWHs